Mean Platelet Volume on Systemic Lupus Erythematosus Patients with and without Thrombocytopenia in Dr Hasan Sadikin Hospital Bandung: A Descriptive Study - Patrick Philo; Laniyati Hamijoyo; Dewi Kartika Turbawaty (Indonesian Rheumatology Association, 2019)
Abstract Background : The aim of the study is to provide an insight about mean platelet volume (MPV) value in systemic lupus erythematosus (SLE) with and without thrombocytopenia patient. MPV wa expected to be used to determine the cause thrombocytopenia in lupus, so the patient could be treated appropriately. Method : The study design was descriptive categoric, and the data were obtained by using cross-sectional method from patient’s medical record and lab examination result in the period from January 1st 2016 – January 31st 2018. The sampling method are done using total sampling. The inclusion criteria of this study were SLE patients which MPV and platelet count had been examined at the same time, the data used is data that was first discovered in the period of the study. The exclusion criteria were incomplete medical record data, patient with thrombocytosis, and SLE with comorbidity such as thrombotic disease (ischemic stroke and deep vein thrombosis), other high inflammatory overlap diseases (such as rheumatoid arthritis and inflammatory bowel disease), and infection. Result : From 75 patients that match with the inclusion criteria, all patients were female and based on the age of diagnosis, most patients were in age group of 25-34 years old (41,33%). Based on the lab results, group with normal platelet count have 53 data of normal MPV and 12 data of high MPV, while group with thrombocytopenia have 6 data of normal MPV and 4 data of high MPV. Conclusion : Group with normal MPV value and normal platelet count has the largest proportion, while the group with thrombocytopenia in lupus and high MPV value has the lowest proportion.